2016
DOI: 10.5713/ajas.16.0575
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lysozyme as a Feed Additive on In vitro Rumen Fermentation and Methane Emission

Abstract: This study was conducted to determine the effect of lysozyme addition on in vitro rumen fermentation and to identify the lysozyme inclusion rate for abating methane (CH4) production. An in vitro ruminal fermentation technique was done using a commercial concentrate to rice straw ratio of 8:2 as substrate. The following treatments were applied wherein lysozyme was added into 1 mg dry matter substrate at different levels of inclusion: Without lysozyme, 2,000, 4,000, and 8,000 U lysozyme. Results revealed that, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
3
Order By: Relevance
“…Mucins and lysozyme are intensively studied in oral human health, but there is a paucity of research on how they may be affected by diet (Emery et al, 1960), and there is a lack of information on their relevance for cattle health. Results from Biswas et al (2016) showing that addition of lysozyme enhanced pH and reduced methane in vitro indicate a microbial-modulating effect of lysozyme in cattle. However, because the lysozyme concentration and activity tended to decrease after the meal, further in vivo research is needed to evaluate the relevance of lysozyme activity on the modulation of the rumen microbiome in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucins and lysozyme are intensively studied in oral human health, but there is a paucity of research on how they may be affected by diet (Emery et al, 1960), and there is a lack of information on their relevance for cattle health. Results from Biswas et al (2016) showing that addition of lysozyme enhanced pH and reduced methane in vitro indicate a microbial-modulating effect of lysozyme in cattle. However, because the lysozyme concentration and activity tended to decrease after the meal, further in vivo research is needed to evaluate the relevance of lysozyme activity on the modulation of the rumen microbiome in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva contains a variety of different proteins with specific biological functions including mucins, lysozymes, and immunoglobulins (Bartley, 1976). Previous research in cattle has indicated the importance of specific salivary components such as foam-dispersing properties of mucin (Bartley and Yadava, 1961), as well as methane-inhibiting and fermentation-enhancing properties of lysozyme in vitro (Biswas et al, 2016). Studies evaluating dietary effects on these salivary bioactive components in cattle are largely lacking in the literature, and it is not clear if the salivary secretions of mucins and lysozyme are affected by grain-rich feeding and its duration.…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 is an indicator of dietary gross energy losses, and it has a negative environmental impact contributing to global warming [ 23 , 24 ]. Previous studies revealed that several factors, including diet, feed additives, host genetics, age, and physiological state affect the rumen microbiomes, rumen fermentation characteristics, and CH 4 production [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. O’Hara et al [ 28 ] reported an association between the rumen microbiome and its fermentation products with feed efficiency and CH 4 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Lysozyme possesses properties for bacterial killing and inflammation elimination, and also is found to prompt virus inactivation (Ferrari et al, 1959;Khalil et al, 1989). It has been used to replace antibiotics as food additives to inhibit bacterial growth, feed additives to prevent feed mildew, and also as antiinfection agent in pharmaceutics (Jollès and Jollès, 1984;Hughey et al, 1989;Biswas et al, 2016). Chicken lysozyme is widely used, while its bacteriolytic activity is almost four times lower than that of human lysozyme (hLYZ) (Ercan and Demirci, 2016).…”
Section: Introductionmentioning
confidence: 99%